Ischemic Stroke - Sanchetee, Pratap (IntechOpen, 2021)
Stroke continues to be a major public health issue. It is the third leading cause of death and disability across the globe. Its early identification and treatment along with prevention are major issues that confront a treating physician. We have understood the importance of early intervention and of the quote 'time is brain'. Our endeavor now should be directed to the public at large and paramedics in particular. Although a stroke is a common condition, the availability of neurologists or stroke specialists is quite scarce. Today, management of a suspected case of stroke is done by a specialist team of medical and paramedical personnel. Advances in imaging, newer therapeutic agents, and endovascular management have revolutionized the management. Currently, we are witnessing a new era in the management of strokes and I am hopeful that continued research will get us to a satisfactory solution. This book along with another book from IntechOpen titled 'Ischemic Stroke of Brain' aims to improve the understanding of stroke medicine for postgraduate medical students in medicine and neurology who have an interest in stroke care.